The effectiveness of social protection for long-term care in old age Is social protection reducing the risk of poverty associated with care needs? - Oliveira Hashiguchi, Tiago Cravo (OECD Health Working Papers, 2020)
As people grow old and their health deteriorates, they are likely to require help with everyday activities that were once second nature; they need what is commonly termed long-term care (LTC). With demand for LTC in old age expected to grow, OECD countries face significant challenges in balancing financial sustainability with the provision of effective social protection against the financial risks associated with developing LTC needs - the cost of care can far exceed median incomes and its duration can be many years. This report provides a novel set of comprehensive and internationally comparable estimates of the adequacy, equity and efficiency of public social protection systems for LTC in old age in OECD countries and EU Member States. Using a set of "typical cases" of LTC need to ensure comparability, including different levels of severity and different ways in which needs can be met, this report shows cross-country and regional variations in the total costs of LTC services, the degree of public coverage, the out-of-pocket costs that care recipients face, and the associated poverty risks. The quantitative results are discussed in the context of how different countries design LTC benefits and schemes, including cost-sharing mechanisms. Finally, to illustrate the policy relevance of the analyses, the distributive effects of actual and hypothetical policy scenarios are simulated, including an international free personal care policy, and possible reforms in Ireland and England